Hibah Perancangan Mesin Pemotong Bonggol Jagung Bagi Masyarakat Petani Jagung di Desa Pamekaran, Kabupaten Sumedang - Sirodz, Muhammad Pramuda Nugraha; Masri, Andry (Suluah Bendang: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2022)
Community service in this paper is a grant from the design of a corn cob processing machine for small and medium industries for corn cob processing, which will be carried out by the Corn Cob Farming Community in the Rancakalong Region, Sumedang Regency. The purpose of this activity is to provide the results of a corncob cutting machine design for corn farming communities in order to increase production capacity for the corncob processing industry into a commodity. This activity begins with analyzing the operation of the existing corncob processing machine and mapping the problems that occur. Based on the results of the field review and analysis carried out, the design of a corncob processing machine that is more efficient and safe is obtained. The results of the design can be duplicated by the community to build a small and medium industry for processing corn cobs as a raw material that is owned in abundance. This activity is part of the Matching Fund program from the Ministry of Education and Culture of the Republic of Indonesia with the Kedaireka platform with the theme of processing corn cobs into raw materials through the use of abundant natural resources from agricultural residues. This activity is based on the results of research, namely the results of an analysis of processing machines that have been used by the existing corncob processing industry in Bandung. The results of the activity show that the community has a machine that can be used as a support for the production process for the established corncob processing industry which is indicated by the existence of a machine prototype that can be felt directly.